Engineered Multilayer Thermal Barrier Coatings for Enhanced Durability and Functional Performance. Issue 9 (28th June 2014) - Viswanathan, Vaishak; Dwivedi, Gopal; Sampath, Sanjay; Troczynski, T.
<x xml:space="preserve">Abstract</x> The durability of plasma sprayed thermal barrier coatings (TBCs) has been of significant interest ever since their introduction in gas turbine engine components. Of particular importance is the role of coating processing, microstructure and ensuing properties on their thermal cycle life. Among the coating properties of the ceramic top coat that have shown strong correlations with durability include the elastic modulus (i.e., compliance) and the fracture toughness, both of which are influenced by processing as well as thermal aging during service. In this article, we have systematically investigated furnace cycle durability of plasma sprayed TBCs produced from controlled processing conditions, yielding differences in both modulus and toughness. Following performance assessment and mechanistic insights obtained from single layer ceramic coatings, novel bilayer architectures have been proposed and fabricated, in an effort to improve furnace cycle durability. The bilayer approach targets coating properties based on location, by providing dense, high toughness coating at regions prone to delamination failure (near‐interface), while allowing for the majority of the coating to contain high porosity, resulting in reduced overall modulus. Such improved bilayers simultaneously display both high durability and low thermal conductivity enabling a promising approach for functionally optimized coatings. The plasma spray process together with its ability to dynamically change process parameters enables the fabrication of these novel architectures.